(untitled) (Research, Society and Development, 2022)
Objective: To identify studies published in the national and international literature on assessing the quality of life of professionals during the COVID-19 pandemic. Methods: Integrative literature review. The studies were searched in the database and MEDLINE/PubMed, EMBASE and Literatura Latino-Americana e do Caribe em Ciências da Saúde-LILACS. The data extracted from the selected articles were evaluated and presented in tables. Results: 12 references were selected from a total sample of 14.215 participants, with the majority of study participants being professional women in the field of nursing. Healthcare professionals working on the frontlines of COVID-19 had low scores on quality of life and significant changes in mental health and symptoms of sleep disorders. Nurses and doctors reported worsening in quality of life. Depression was also identified in studies as a consequence of this pandemic period, regardless of whether the professional worked directly with a patient diagnosed or suspected of having COVID-19. Females had a worse quality of life. Professionals over 40 years of age had a lower score for quality of life. Conclusion: Health professionals had an impaired quality of life in the period of the COVID-19 pandemic in Brazil, especially professionals who work on the front line.